Aftershocks of the Samarco disaster: diminished growth and increased metal content of Raphanus sativus cultivated in soil with mining tailings - Araújo, Bárbara Dias; Maia, Renata; Arantes-Garcia, Lucas; Oki, Yumi; Negreiros, Daniel; Assis, Igor Rodrigues de; Fernandes, Geraldo Wilson (Acta scientiarum. Biological sciences, 2022)
The collapse of the Fundão tailings dam of the Samarco mining complex in Mariana, Brazil, was the largest mining disaster in the world to date with many socio-economic and environmental impacts. Soil affected by mining tailings was severely altered with negative impacts for agriculture. We tested whether diluting mining tailings with organic soil would eliminate or at least attenuate the ecotoxic effects on plant development and performance. We cultivated radish, Raphanus sativus, in substrates containing different proportions of mining tailings and organic soil: pure tailings (T100%); 2) tailings75% + soil25% (T75%); 3) tailings50% + soil50% (T50%); 4) tailings25% + soil75% (T25%), and 5) pure organic soil (Soil100%, control). There were large differences in soil quality parameters between the 100% tailings treatment (T100%) and the control (Soil100%), as well as for some parameters in the most diluted treatment - T25% (Ca2+, Fe, Mn) in relation to the control treatment. Although dilution of the tailings soil improved radish development, there was lower radish productivity (leaf area, total biomass, and root/tuber biomass) than for pure soil (control). There were also significantly higher amounts of bioaccumulated metals in radish tubers grown with tailings, even when grown in T25% for Fe content and in T75% for Mn content. These results present a worrisome scenario for human communities in the region of the Doce river, as human consumption of crops produced in soil contaminated with tailings is not recommended due to potential toxicological effects from high metal concentrations.